Microbial environment, immunity and human health - Gerber, G. (Екологічна безпека та природокористування, 2008)
Sophisticated analytical tools for elucidating genome structure and life of bacteria yielded a new paradigm on our relation to the microbial environment. Formerly, bacteria were seen as jeopardising invaders, and studies on bacterial pathogenesis were the basis for great medical progress in the restraint of infections. Now it becomes clear that Homo sapiens is not a single-species organism, but it is to understand as a complex ecosystem assembled of a 10:1 mixture of both environmental microbial and human cells.